Breaking barriers: in depth analysis of gym accessibility among gym goers, including individuals with disabilities and those who train them - Beattie, Cassandra Maria (Kansas State University, 2024)
Background: Nearly 80% of US adults do not meet physical activity guidelines. Yet, over a quarter of US adults hold a gym membership. Gyms are locations dedicated to physical activity participation, yet barriers persist negatively influencing gym-based physical activity (i.e., exercise). Individuals with disabilities (IWD) are less likely to participate in exercise behaviors as compared to their non-disabled counterparts. IWD battle their own unique set of barriers to gym-based exercise. Most gyms lack disability-educated staff, including personal trainers, further limiting the exercise opportunities for IWD. Exercise is essential for the health and wellness of IWD and those without disabilities. Therefore, the purpose of this dissertation is three-fold: Study one) How do gym-goers describe their gym experiences? Study two) How do individuals with congenital and acquired disabilities manage to overcome barriers to gym-based exercise? Study three) How have personal trainers managed to successfully overcome barriers to training IWD? Methods: This dissertation compromises three studies (Chapters 2, 3, 4). The first study utilized a qualitative design consisting of eleven semi-structured focus groups (33 participants) to explore the experiences of gym goers to better understand what facilitates or poses barriers to their gym attendance. A hybrid inductive-abductive approach and thematic content analysis was employed to interpret participant responses. The second study utilized a qualitative study design consisting of 10 individual interviews to determine gym-based exercise facilitators and barriers from the perspective of individuals with congenital and acquired disabilities meeting, surpassing, or partially meeting physical activity guidelines. A thematic content analysis was employed to interpret participant responses. Lastly, study three also utilized a qualitative study design with a thematic content analysis to explore the experiences of 10 personal trainers of differing educational and occupational background successfully training IWD. Results: Chapter 2’s inductive, thematic content analysis of focus group data revealed three themes regarding gym experiences: 1) experiencing discrimination negatively affects gym satisfaction and attendance 2) inclusive design facilitates gym satisfaction and attendance, and 3) alliances help and hinder gym satisfaction and attendance. A sense of belonging was found as an underlying element across all themes. Building on the inductive, thematic content analysis findings, an abductive approach was utilized to propose a new, adapted model called, “Belonging in the Gym,” based on the original, “Belonging in Academia Model.” In chapter 3 three themes were found regarding facilitators and barriers to gym-based exercise for IWD: 1) barriers and facilitators to gym use by IWD extend beyond gym layout, 2) experiences with other gym members are both positive and negative, and 3) personal trainers need special training, but should not apply special treatment when working with IWD. Chapter 4’s findings expanded upon the third theme from Chapter 3 by exploring the diverse experiences of personal trainers who were currently training IWD. Personal trainers’ insights were condensed into five themes that provide knowledge on how to better support the training of IWD and include: (1) specialized education and extended experience are needed for personal trainers working with IWD, (2) experience working with a diverse range of disabilities and differing expressions of each is vital for personal trainers’ success in working with IWD, (3) an active network between personal trainers and allied healthcare providers is necessary to better support clients, (4) resource management is a must for personal trainers to improve accessibility to physical activity, and (5) personal trainers empower IWD to self-advocate for their physical activity needs. Conclusion: A sense of belonging both facilitates and serves as a barrier for gym experiences, influencing overall attendance and exercise behaviors of gym goers. Gym-goers with disabilities successfully completing exercise behaviors explain that influences for their exercise extend beyond gym layout, to include positive and negative experiences with fellow gym-goers and personal trainers. Personal trainers affirmed that many IWD have negative experiences with other trainers and additional education, experience, networking, and advocation is needed to change that. Personal trainers may be the most influential gym staff members to intervene with by utilizing educational interventions. Given the lack of public health interventions within gyms spaces, it is critical to conduct future research to expand the accessibility of gyms and further increase exercise behaviors among US adults.
Keywords: Sense of belonging; Personal trainers; Adaptive exercise; Impairments